Design of Drip Irrigation System in a Study Area - Riyam Sabri Hasan; Prof. Ibrahim Motawa; Prof. Hossam A. AbdelGawad (Genius Journals, 2023)
The finest irrigation technique in use today, among all irrigation techniques, is drip irrigation, thanks to its excellent and high consistency. This technique uses a pipe network to carry water to the field, then emitters to change it into energy for the plant. Despite the benefits of drip irrigation, there are several issues with the conventional network, including how the distribution of discharges, silt, and soil type affects the system. The location and rate of water supply in the root zone must be coordinated with crop needs in order for a drip irrigation system to fulfill its objectives . The goal of the study is to is to design a drip irrigation system as a means of availing water for irrigation using crop data, consumptive use and soil data . Fieldwork methodology and theoretical approach are the two methodologies that the study uses. In field work, soil analysis is done to look at the physical and chemical characteristics of the soil that have an impact on its quality and its appropriateness for growing plants. A study of soil testing was carried out in an engineering laboratory to monitor the functioning of this system. Regarding the theoretical strategy a well-known piece of software called CROPWAT was used to calculate the crop water requirements and irrigation requirements based on soil, climate, and crop data. In estimation of the consumptive use, flow velocity, discharge, running time, distance between two drips, wetted soil width, wetted soil depth, frequency of irrigation for clay and sand soil.
Keywords: drip irrigation; soil type; CROPWAT; discharge; wetted depth